Analisis Pengambilan Keputusan dalam Kendala di UMKM Sultan Smoothies Kota Karawang - Denanda Alivia Fasha; Delia Sri Wahyuni; Gita Prameshia Wulandari; Lia Nur Andini; Ujang Suherman (STIKes Ibnu Sina Ajibarang, 2025)
MSMEs (Micro, Small, and Medium Enterprises) have an important role in boosting the regional economy, including in Karawang City. One of the MSMEs that attracted attention was Sultan Smoothies, which focuses on selling healthy drinks made from fresh fruits. This research aims to identify the availability of competent workforce, analyze business capital management, evaluate raw material management, and examine marketing strategies applied to support business operations optimally. The location of the research was determined deliberately. Sunday, December 8, 2024. The place is on Jl. HS Ronggo Waluyo, Sukaharja Teluk Jambe Timur, Karawang Regency. This research uses a qualitative method with a study approach. Data analysis was carried out throughout this study and was carried out continuously from the beginning to the end of the study. This research process is in the form of a cycle including data collection, data display, data reduction, and conclusion drawn. The results of the study show that the smoothies business run by Muhammad Rizal is an inspiring example of young entrepreneurs who dare to take risks to achieve financial independence. Despite facing various challenges, he was able to persevere and devise strategies for long-term growth.